Occupational Asthma in Hospital Healthcare Worker - Rahmad Budianto; Tri Wahju Astuti (Jurnal Respirologi Indonesia, 2020)
Occupational asthma is defined as an adult onset of asthma triggered by specific exposures or combinations from the workplace. Occupational asthma is classified into a sensitizer-induced occupational asthma or allergic occupational asthma caused by exposure or sensitization by a causative agents induced by immunological reactions; and irritant-induced occupational asthma or non-allergic occupational asthma caused by agents that are irritative to the airway. Occupational asthma can occur in health workers at hospitals. In the hospital there are various exposure of agents, medicines, and health equipments which can induce the asthma symptoms for health workers. The diagnosis of occupational asthma established by history taking, physical examination, supporting examination (spirometry, bronchial hyper-responsiveness test, exhaled nitric oxide, and immunological tests), and biomarker test. Management of occupational asthma includes principle management by avoiding exposure, pharmacological therapy, and immunotherapy. Precautions taken by primary, secondary (medical surveilance) and tertiary prevention (prevention of disability through worker’s compensation system).